1975
DOI: 10.1177/000348947508400616
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predisposing Factors and Outcome of Pharyngocutaneous Fistulas Complicating Head and Neck Cancer Surgery

Abstract: A major complication of head and neck cancer surgery following radiation and extensive resection is pharyngocutaneous fistula. A retrospective analysis of 36 fistula patients out of 376 major head and neck procedures between January 1971 and July 1973 revealed certain guidelines for improved clinical management. Since a large discrepancy existed in the incidence of fistulas between the different surgical procedures, each operative group was examined separately. The incidence, predisposing factors, and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 10 publications
0
49
1
2
Order By: Relevance
“…As a comparison, pharyngocutaneous fistulas after laryngectomy without previous therapy occurred in about 11% for hypopharyngeal [32] and in 4% for laryngeal carcinomas [33].…”
Section: Discussionmentioning
confidence: 97%
“…As a comparison, pharyngocutaneous fistulas after laryngectomy without previous therapy occurred in about 11% for hypopharyngeal [32] and in 4% for laryngeal carcinomas [33].…”
Section: Discussionmentioning
confidence: 97%
“…The reported incidence of pharyngocutaneous fistula ranges from 5 to 65 % [4][5][6][7][8]. Its occurrence vastly increases the length of stay and consequently, the costs of treatment [5].…”
Section: Discussionmentioning
confidence: 99%
“…It leads to increased morbidity, delay in adjuvant treatment, prolonged hospitalization, and increased treatment costs [3]. The reported incidence of pharyngocutaneous fistula is extremely variable in the literature ranging from 5 to 65 % [4][5][6][7][8] but rate between 12 and 30 % has been often reported.…”
Section: Introductionmentioning
confidence: 99%
“…Five of 8 fistulae occurred in 11 patients who had undergone prior radiation therapy. Since Stell et al [24] and Dedo et al [25] have shown that the risk of fistula after laryngectomy is considerably higher in irradiated patients, we would caution against the use of the stapler in patients who have received radiation. Also the use of stapling devices is probably not indicated after laryngopharyngeetomy performed for treatment of piriform sinus cancer.…”
Section: Discussionmentioning
confidence: 99%